2018
DOI: 10.1002/chem.201803842
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a 3D MnII‐Metal–Organic Framework Based on a Nonmetallated Porphyrin Linker for Selective Capture of CO2 and One‐Pot Synthesis of Styrene Carbonates

Abstract: A 3D Mn -porphyrin metal-organic framework (MOF), [{Mn (TCPP)⋅2H O}⋅DMF] (MOF1) (TCPP=5,10,15,20-tetrakis(4-benzoate)porphyrin), was constructed; it exhibits an interesting 3D framework structure with two types of 1D channels of dimensions of 3.94×8.37 Å and 4.66×4.93 Å running along the crystallographic a axis. Owing to the presence of a nonmetallated porphyrin cavity, MOF1 exhibits selective storage of CO with an isosteric heat of adsorption value of 32.1 kJ mol , which is further supported by theoretical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 100 publications
2
24
0
Order By: Relevance
“…Based on these results and some literature reports, [21][22][23] a possible radical pathway involved mechanism in our case was proposed and depicted in Scheme 1. First, open Ce 4 + sites of CSUST-3 react with TBHP to produce Ce 5 + -peroxy adducts, which next release t-butoxy radicals and regenerate Ce 4 + sites.…”
Section: Chemsuschemsupporting
confidence: 65%
See 2 more Smart Citations
“…Based on these results and some literature reports, [21][22][23] a possible radical pathway involved mechanism in our case was proposed and depicted in Scheme 1. First, open Ce 4 + sites of CSUST-3 react with TBHP to produce Ce 5 + -peroxy adducts, which next release t-butoxy radicals and regenerate Ce 4 + sites.…”
Section: Chemsuschemsupporting
confidence: 65%
“…The slightly lower efficiencies gave by 4-chlorostyrene and 4-methylstyrene are consistent with the trend reported in literature. [21,23] When 4-tert-butylstyrene with a bulky tert-butyl group used, lower yield (36 %) were obtained, which may be due to the size effect of MOF catalysis.…”
Section: Chemsuschemmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Inspired by these works, Nagaraja and coworkers synthesized a novel Mn(II)-porphyrin metal-organic framework, [{Mn 2 (TCPP)$2H 2 O}$DMF]n (MOF1) through the reaction of Mn(NO 3 ) 2 $6H 2 O and H 4 TCPP ligand under the solvothermal conditions. 36 Single crystal X-ray structural determination revealed that MOF1 crystallizes in the monoclinic crystal system with a centrosymmetric P2 1 /n space group and features a 3D architecture constituted by binuclear Mn(II) nodes and non-metallated porphyrin ligand. Interestingly, the nonmetallated nature of porphyrin ring was exploited for the implantation of Lewis acidic Fe(III) ions to generate Fe(III) @MOF1 material.…”
Section: Metal-catalyzed Reactionsmentioning
confidence: 99%
“…[ 9,13–15 ] Recent studies that focus on this feature include porphyrin‐based conjugated microporous polymers (CMPs) with azide groups, [ 16 ] a porphyrin‐ and pyrene‐based CMP (Por–Py–CMP), [ 14 ] a triazine‐functionalized porphyrin‐based porous organic polymer (TPOP‐1), [ 17 ] and 3D Mn II ‐porphyrin metal–organic framework (MOF). [ 18 ] Porphyrin‐based porous structures also show ability to store hydrogen (H 2 ) gas. [ 13,19,20 ] Polyporphyrins with high surface areas (e.g., over 1500 m 2 g −1 ) and functionalized with thiophenyl groups showed 5% mass increase after H 2 adsorption at 77 K and 65 bar.…”
Section: Introductionmentioning
confidence: 99%